PENDAMPINGAN KREATIVITAS KULIT BAMBU DAN STRATEGI PEMASARAN PENGRAJIN BAMBU MASYARAKAT DESA TELUK PANJI 1 KABUPATEN LABUHANBATU SELATAN - Ani Purwanti; Abdul Halim; Yudi Prayoga (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The presence of bamboo in human life seems to provide a blessing for the people of Indonesia, this is because bamboo is one of the natural resources that can be utilized and has the potential to be managed into handicrafts. The main reason for this community service is to develop an economically independent community, to provide ideas and creativity, and enthusiasm in the form of morals to the community, to develop the business currently engaged in so that they can survive through the knowledge gained by lectures through marketing. The positive results obtained from this community service activity are to raise the sensitivity and concern of Higher Education through students in helping solve problems and provide solutions faced by the community, in addition to opening up students so that they can interact with partners or the community socially. For the people of Teluk Panji I Village, South Labuhanbatu Regency, especially bamboo skin craftsmen, through this activity, woven leather products such as baskets, Tampa, satay fans, household fans, and others are quite good in terms of functionality and have economic value. Bamboo skin woven products to have added value must have innovation and quality, this is necessary because handicraft products are jobs that require expertise so that the final product process must really be maintained and even improved